2001
DOI: 10.1597/1545-1569(2001)038<0379:qoliaw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Adults With Repaired Complete Cleft Lip and Palate

Abstract: The CLP group perceived a marked impact of the handicap on their lives concerning global aspects, well-being, and social life. More practical and tangible aspects of their daily living, however, were not affected, and only some minor aspects of their quality of life in general were poor in comparison with the control group, which indicates a fairly good life adjustment in spite of the handicap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 23 publications
6
83
0
12
Order By: Relevance
“…Part of the treatment for clefting extends throughout adolescence, during which psychological adjustment has been reported to be a problem as well (Kapp-Simon et al, 1992;Thomas et al, 1997). Lower psychological adjustment, cognitive performance, as well as social and economic achievement in processes such as marriage, educational attainment, and income level, have been reported as well among adults with oral clefts in several studies (Heller et al, 1981;Bjornsson and Agustsdottir, 1987;Ramstad et al, 1995aRamstad et al, , 1995bMarcusson et al, 2001; Nopolous et al, 2002). No studies have reported the impact of clefting on the quality of life of infants.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Part of the treatment for clefting extends throughout adolescence, during which psychological adjustment has been reported to be a problem as well (Kapp-Simon et al, 1992;Thomas et al, 1997). Lower psychological adjustment, cognitive performance, as well as social and economic achievement in processes such as marriage, educational attainment, and income level, have been reported as well among adults with oral clefts in several studies (Heller et al, 1981;Bjornsson and Agustsdottir, 1987;Ramstad et al, 1995aRamstad et al, , 1995bMarcusson et al, 2001; Nopolous et al, 2002). No studies have reported the impact of clefting on the quality of life of infants.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…6 These instruments have the potential to improve the quality of clinical and psychosocial care. 7 Orofacial function includes vital actions (e.g., breathing, chewing and swallowing) and muscle posture (e.g., mouth and tongue posture) 8 and forms the basis for social interaction in terms of speech, emotional communication, facial expression and appearance. 9 Orofacial dysfunctions can compromise well-being and OHRQoL from childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Wenn die Spalte eines Kindes sichtbar ist, können Familien negative so ziale Reaktionen wegen des ungewöhnlichen Aussehens ihres Kindes erfahren [3]. Die aufwendige und sich über einen langen Zeitraum erstreckende Behandlung und die möglichen psychosozialen Belastungen durch die Spaltbildung haben unter Umständen einen bleibenden Einfluss auf das Wohlbefinden und die Lebensqualität des Patienten [23].…”
Section: Introduction Einleitungunclassified